The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1471-2458-11-872
|View full text |Cite
|
Sign up to set email alerts
|

Increasing safer sexual behavior among Lao kathoy through an integrated social marketing approach

Abstract: BackgroundAlthough HIV prevalence has remained low in Laos thus far, there is reason to be concerned that Lao male-to-female (MtF) transgender persons (kathoy) and their partners may facilitate the spread of HIV. Little is known about how to most effectively reach kathoy with HIV prevention programming. This paper evaluates an intervention with Lao kathoy with the objective of increasing safe sex with regular and casual partners.MethodsQuantitative surveys were administered in November 2004 (n = 288) and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…Table 1 describes detail characteristics of the selected studies and their study population. Of the five included studies, three were conducted in Thailand (Kasatpibal et al, 2014;Pawa et al, 2013;Rongkavilit et al, 2013), one in Vietnam (Oldenburg et al, 2014), and one in Laos (Longfield, Panyanouvong, Chen, & Kays, 2011). Only three of the included studies had both baseline and follow-up intervention data (Longfield et al, 2011;Oldenburg et al, 2014;Rongkavilit et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 describes detail characteristics of the selected studies and their study population. Of the five included studies, three were conducted in Thailand (Kasatpibal et al, 2014;Pawa et al, 2013;Rongkavilit et al, 2013), one in Vietnam (Oldenburg et al, 2014), and one in Laos (Longfield, Panyanouvong, Chen, & Kays, 2011). Only three of the included studies had both baseline and follow-up intervention data (Longfield et al, 2011;Oldenburg et al, 2014;Rongkavilit et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Of the five included studies, three were conducted in Thailand (Kasatpibal et al, 2014;Pawa et al, 2013;Rongkavilit et al, 2013), one in Vietnam (Oldenburg et al, 2014), and one in Laos (Longfield, Panyanouvong, Chen, & Kays, 2011). Only three of the included studies had both baseline and follow-up intervention data (Longfield et al, 2011;Oldenburg et al, 2014;Rongkavilit et al, 2013). Three studies targeted MSM (Kasatpibal et al, 2014;Oldenburg et al, 2014;Rongkavilit et al, 2013), and two observed transwomen (Longfield et al, 2011;Pawa et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enabling environment is referenced in research without defining it [36][37][38][39][40][41], creating the perception that it is a universally understood term with a common definition. One assumption about the enabling environment is that it is dependent on desired outcomes.…”
Section: What Is An Enabling Environment?mentioning
confidence: 99%